Refining details of the structural and electronic properties of the CuB site in pMMO enzyme through sequential molecular dynamics/CPKS-EPR calculations. Issue 27 (22nd June 2022) - Da Silva, William Daniel B.; Dias, Roberta P.; Da Silva, Júlio C.S.
Abstract : MD/CPKS-computational results support recent EPR-experimental data interpretations proposing that pMMO's CuB -site is an octahedral complex containing two waters axially bound. Abstract : This work investigated the structural and electronic properties of the copper mononuclear site of the PmoB part of the pMMO enzyme at the molecular level. We propose that the CuB catalytic site in the soluble portion of pMMO at room temperature and under physiological conditions is a mononuclear copper complex in a distorted octahedral arrangement with the residues His 33, His 137, and His 139 on the equatorial base and two water molecules on the axial axis. Our view was based on the molecular dynamics results and DFT calculations of the electronic paramagnetic resonance parameters and comparisons with experimental EPR data. This new proposed model for the CuB site brings additional support concerning the recent experimental evidence, which pointed out that a saturated coordination sphere of the copper ion in the CuB center is an essential factor that makes it less efficient than the CuC site in the methane oxidation. Therefore, according to the CuB site model proposed here, an additional step involving a displacement of at least one water molecule of the copper coordination sphere by the O2 molecule prior to its activation must be necessary. This scenario is less likely to occur in the CuC center once this one is buried in the alpha-helices, which are part of the pMMO structure bound to the membrane wall, and consequently located in a less solvent-exposed region. In addition, we also present a simple and efficient sequential S-MD/CPKS protocol to compute EPR parameters that can, in principle, be expanded for the study of other copper-containing proteins.